The Effect of Evaluation on Teacher Performance - Taylor, Eric S; Tyler, John H (American Economic Review, 2012)
Teacher performance evaluation has become a dominant theme in school reform efforts. Yet, whether evaluation changes the performance of teachers, the focus of this paper, is unknown. Instead, evaluation has largely been studied as an input to selective dismissal decisions. We study mid-career teachers for whom we observe an objective measure of productivity—value-added to student achievement—before, during, and after evaluation. We find teachers are more productive in post-evaluation years, with the largest improvements among teachers performing relatively poorly ex-ante. The results suggest teachers can gain information from evaluation and subsequently develop new skills, increase long-run effort, or both.